Mechanics of dust bathing in birds - Po-Lin Kuo; Guan-Yu Chen; Yu-Chia Fan; Wing-Ying Wan; Patricia J. Yang (Proceedings of the National Academy of Sciences, 2026)
Dust bathing is a widespread behavior among birds that helps remove ectoparasites, but its mechanical basis remains poorly understood. Here we show that wing flapping during dust bathing generates sand-particle collisions sufficient to dislodge feather mites. Using high-speed video analysis across 34 bird species, we found that wing-flapping frequency scales inversely with body mass ( f ∼ M - 0.20 ), ranging from 1 to 10 Hz. Since feather motion matches wing motion, we use mechanical shakers to simulate dust-bathing dynamics. Mite-removal experiments reveal that parasite dislodgment efficiency increases rapidly up to around 5 Hz and plateaued thereafter. The frequencies around 5 Hz are sufficient to achieve maximal cleaning efficacy. Collision modeling indicates that the impact force from sand particles exceeds mite adhesion forces, thus collision is the dominant removal mechanism. Mites are removed within seconds when sand is present, suggesting that sand plays an active mechanical role in parasite dislodgment. These findings not only elucidate a physical mechanism underlying dust bathing, but also suggest that birds may have evolutionarily tuned their flapping behavior to optimize parasite removal through substrate interaction.